62‐1: Invited Paper: Highly Stable Self‐Aligned Coplanar InGaZnO Thin‐Film Transistors and Investigation on Effective Channel Length†. Issue 1 (29th May 2019) - Kim, Jung Bae; Lim, Rodney; Tsai, Yun-chu (Pipi); Wang, Jiarui; Zhao, Lai; Choi, Soo Young; Bender, Marcus; Yim, Dong Kil
Abstract : Highly stable top‐gate InGaZnO (IGZO) thin‐film transistors (TFTs) with excellent threshold voltage (Vth) uniformity are developed by optimizing gate insulator film properties and controlling oxygen/hydrogen diffusion into IGZO channel. The TFTs do not show notable negative Vth shift and Vth non‐uniformity from channel length 10 µm down to 3 µm.